Electrochemical Activity of Methionine at Graphite Electrode Modified with Gold Nanoparticles; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Perevezentseva D. O. Dariya Olegovna; Skirdin K. V. Kirill Vyacheslavovich; Gorchakov E. V.; Bimatov V. I. (Advanced Materials and Alloys, Nanomaterials and Nanotechnology, 2016)
Title screen